The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1111/j.1365-2958.2008.06448.x
|View full text |Cite
|
Sign up to set email alerts
|

Actin‐depolymerizing factor, ADF/cofilin, is essentially required in assembly of Leishmania flagellum

Abstract: SummaryADF/cofilins are ubiquitous actin dynamics-regulating proteins that have been mainly implicated in actinbased cell motility. Trypanosomatids, e.g. Leishmania and Trypanosoma, which mediate their motility through flagellum, also contain a putative ADF/cofilin homologue, but its role in flagellar motility remains largely unexplored. We have investigated the role of this protein in assembly and motility of the Leishmania flagellum after knocking out the ADF/cofilin gene by targeted gene replacement. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
106
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(113 citation statements)
references
References 56 publications
4
106
1
2
Order By: Relevance
“…in Pfam, which is considered to be one of the most reliable domain databases, the seed sequence alignment is shifted in the case of the N-terminal end of human cofilin-1, which results in a less descriptive domain definition for the ADF-H domain. (Tammana et al, 2008;Yeoh et al, 2002) M. musculus ADF YES (RbskACT, platelet) YES (RbskACT, platelet) YES (platelet) ND (Vartiainen et al, 2002) M. musculus cofilin-1 (nm)…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…in Pfam, which is considered to be one of the most reliable domain databases, the seed sequence alignment is shifted in the case of the N-terminal end of human cofilin-1, which results in a less descriptive domain definition for the ADF-H domain. (Tammana et al, 2008;Yeoh et al, 2002) M. musculus ADF YES (RbskACT, platelet) YES (RbskACT, platelet) YES (platelet) ND (Vartiainen et al, 2002) M. musculus cofilin-1 (nm)…”
Section: Discussionmentioning
confidence: 99%
“…NO (human platelet) ND ND (Singh et al, 2011) T. gondii TgADF (Tammana et al, 2008;Yeoh et al, 2002) M. musculus ADF YES/ADP (RbskACT) ND (Vartiainen et al, 2002) M. musculus cofilin 1 (nm) YES/ADP (RbskACT) ND (Vartiainen et al, 2002) M. musculus cofilin 2 (m) YES/ADP (RbSKACT) ND (Vartiainen et al, 2002) stimulation (human platelet, bovine beta, PfACT) (Schüler et al, 2005a;Singh et al, 2011) P. berghei PbADF2 YES/? (human platelet) stimulation (human platelet) (Singh et al, 2011) T. gondii TgADF YES/?…”
Section: Tablesmentioning
confidence: 99%
“…Detailed characterization of Leishmania ADF/cofilin (Cof) revealed that it readily binds both the monomeric and filamentous (Kapoor et al, 2008) forms of Leishmania actin and also depolymerizes filamentous actin into monomers (Tammana et al, 2008). Furthermore, it displays high nucleotide exchange but weak actin-filament-severing activities (Tammana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Leishmania parasites express only one isoform of ADF/cofilin, which is essentially required in flagellar assembly and motility (Tammana et al, 2008). Detailed characterization of Leishmania ADF/cofilin (Cof) revealed that it readily binds both the monomeric and filamentous (Kapoor et al, 2008) forms of Leishmania actin and also depolymerizes filamentous actin into monomers (Tammana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation